2010
DOI: 10.2337/db10-0162
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Overfeeding May Induce Peripheral Insulin Resistance Without Altering Subcutaneous Adipose Tissue Macrophages in Humans

Abstract: OBJECTIVEChronic low-grade inflammation is a feature of obesity and is postulated to be causal in the development of insulin resistance and type 2 diabetes. The aim of this study was to assess whether overfeeding induces peripheral insulin resistance in lean and overweight humans, and, if so, whether it is associated with increased systemic and adipose tissue inflammation.RESEARCH DESIGN AND METHODSThirty-six healthy individuals undertook 28 days of overfeeding by +1,250 kcal/day (45% fat). Weight, body compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
92
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 41 publications
9
92
2
1
Order By: Relevance
“…39 An overfeeding challenge rapidly installed an insulin-resistant state in healthy subjects, despite the fact that no significant change occurred in the total macrophage accumulation in the adipose tissue and that there was no change in the number of circulating cells. 40 Additionally, we found that irrespective of the degree of insulin resistance in morbid obesity, macrophage accumulation in omental adipose tissue was associated with the severity of liver fibroinflammation, a well-known and severe complication of obesity. 38 Although the potential link between adipose tissue macrophages and cardiovascular complications in obesity has not been explored yet, several reports have indicated that there is a link between increases in CD16 ϩ monocyte subsets and the development of cardiovascular events 14 -17 and coronary fibrous cap thickness in patients with unstable angina pectoris.…”
Section: Cd16mentioning
confidence: 71%
“…39 An overfeeding challenge rapidly installed an insulin-resistant state in healthy subjects, despite the fact that no significant change occurred in the total macrophage accumulation in the adipose tissue and that there was no change in the number of circulating cells. 40 Additionally, we found that irrespective of the degree of insulin resistance in morbid obesity, macrophage accumulation in omental adipose tissue was associated with the severity of liver fibroinflammation, a well-known and severe complication of obesity. 38 Although the potential link between adipose tissue macrophages and cardiovascular complications in obesity has not been explored yet, several reports have indicated that there is a link between increases in CD16 ϩ monocyte subsets and the development of cardiovascular events 14 -17 and coronary fibrous cap thickness in patients with unstable angina pectoris.…”
Section: Cd16mentioning
confidence: 71%
“…Furthermore, consistent with our hypothesis, we show that an increase in lipid metabolites are associated with defects in tissue insulin action, suggesting that lipotoxicity is a generalised mechanism associated with the induction of insulin resistance in individual tissues of mice. Studies in rodents [7,[19][20][21]23], dogs [24] and humans [25][26][27], have shown that short-term exposure to HFD/overfeeding (3-28 days) results in the rapid development of insulin resistance and glucose intolerance. Often these changes occur with only modest increases in fat mass, highlighting that metabolic defects occur prior to the onset of obesity and do not require extensive periods of fat feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Blood was collected at 1, 3, 4, 5, 6, 7, 8, and 10 min after glucose infusion. Insulin sensitivity was then measured using a 2-h hyperinsulinemic-euglycemic clamp (80 mU/m 2 /min), as described previously (14).…”
Section: Metabolic Tests In Participantsmentioning
confidence: 99%